(3GdOHdheGSjI GdeYGUQI (B:s (3OQGSI bGfhfjI (B= Contemporary diplomatic :a comparative study /s - (3UHGQjfj, ZGRj MSf,s 1949- ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2017)
(3EPG cGfJ GdSjGSI GdNGQLjI gj eLehYI GdbQGQGJ hGdSjGSGJ GdJj JMOO HgG cd OhdI ehGbagG hhLgGJ fXQgG aj GdYdGbGJ GdOhdjI, aEf GdOHdheGSjI gj Gdafhf hGdhSGFd hGdCSGdjH GdJj JfaP HgG GdOhdI SjGSJgG GdNGQLjI, hdPdc JTZd GdOHdheGSjI eQcRG QFjSjG aj eLGd GdSjGSI GdNGQLjI, hegeG jcf ef CeQ abO GJSY fWGb GdOHdheGSjI GdJbdjOjI (B((3GdHYKGJ GdOHdheGSjI hGdbfUdjI(B) (3OHdheGSjI GdeDJeQGJ hGdefXeGJ GdOhdjI GdJj jWdb YdjgG GdOHdheGSjI GdLeGYjI(B. (3hbO CJGMJ GdeDJeQGJ GdOhdjI hGdGLJeGYGJ GdJj JYbOgG GdefXeGJ GdOhdjI aQUI cHjQI defOhHj GdOhd ELQGA eMGOKGJ ZjQ QSejI hefGbTI GdeTGcd GdJj Jge HdGOge hGJNGP GdbQGQGJ GdeTJQcI hSjQG eY efWb GdHMK, abO Je JbSje HMK GdOHdheGSjI GdeYGUQI (B((3OQGSI bGfhfjI(B) (3Edi GdCHhGH GdJGdjI (B: (3HGH JegjOj GdJYQja HGdOHdheGSjI, GdHGH GdChd GdJeKjd GdOHdheGSj, GdHGH GdKGdK GdOHdheGSjI GdLeGYjI(B. (3hbO QhYj aj gPg GdOQGSI Cf Jchf ChdG OQGSI fXQjI abgjI dJchf NjQ eYjf dWdGH cdjGJ GdMbhb hGdeYGgO GdYdjG ddOQGSGJ GdOHdheGSjI, hKGfjG Jchf OQGSI JWHjbjI YedjI JdGFe WHjYI GdYed GdOHdheGSj hJhGLg ebJVjGJg heJWdHGJg, hJchf eQLYG ddYGedjf aj hRGQGJ GdNGQLjI aj GdhWf GdYQHj(B.s
(3edGMb (B: (3UaMI (B317-454.s
(3HHdjhLQGajI (B: (3UaMI (B455-458.s
Keywords: (3GdOHdheGSjI (B((3bGfhf Ohdj(B)s; (3GdSjGSI GdOhdjIs; (3GdOHdheGSjIs -- (3bhGfjf hJTQjYGJs